Late prematurity: a systematic review - Luís Carlos Machado Júnior; Renato Passini Júnior; Izilda Rodrigues Machado Rosa (Jornal de Pediatria (Versão em Português), 2014)
Objective: this study aimed to review the literature regarding late preterm births (34 weeks to 36 weeks and 6 days of gestation) in its several aspects. Sources: the MEDLINE, LILACS, and Cochrane Library databases were searched, and the references of the articles retrieved were also used, with no limit of time. Data synthesis: numerous studies showed a recent increase in late preterm births. In all series, late preterm comprised the majority of preterm births. Studies including millions of births showed a strong association between late preterm birth and neonatal mortality. A higher mortality in childhood and among young adults was also observed. Many studies found an association with several neonatal complications, and also with long-term disorders and sequelae: breast-feeding problems, cerebral palsy, asthma in childhood, poor school performance, schizophrenia, and young adult diabetes. Some authors propose strategies to reduce late preterm birth, or to improve neonatal outcome: use of antenatal corticosteroids, changes in some of the guidelines for early delivery in high-risk pregnancies, and changes in neonatal care for this group. Conclusions: numerous studies show greater mortality and morbidity in late preterm infants compared with term infants, in addition to long-term disorders. More recent studies evaluated strategies to improve the outcomes of these neonates. Further studies on these strategies are needed.